Roles of a protease from Euphorbia resinifera latex in human anticoagulant and antithrombotic activities. (25th September 2020) - Siritapetawee, Jaruwan; Khunkaewla, Panida; Thumanu, Kanjana
Abstract: Thromboembolism is a major cause of morbidity and mortality worldwide. Most therapeutic drugs for treating thrombosis can cause hemorrhage and have short half-lives within human blood circulation resulting in a need to discover and develop novel anticoagulants/antithrombotics. EuRP-61 has been isolated from a plant latex ( Euphorbia resinifera ) and characterized as a serine protease. In this study, EuRP-61 was able to hydrolyze all chains of human fibrin clots. The enzyme may have long term stability in blood circulation as its fibrinogenolytic activity was not affected by human blood circulating inhibitors such as α2 -macroglobulin and antithrombin III. The enzyme may affect the extrinsic, intrinsic or common pathways of the human blood coagulation cascade as evidenced by its prolonged of both prothrombin (PT) and activated partial thromboplastin (APTT) time. Moreover, the enzyme inhibited platelet aggregation via the ADP-receptor pathway. EuRP-61 was not toxic to human red blood cells in the 4 common blood groups (A, B, O and AB) (all Rh + ) or human peripheral blood mononuclear cells (hPBMCs). The enzyme may protect human peripheral blood cells from aggregation without destroying them. This study provides evidence that EuRP-61 may have potential as an agent for the treatment of thrombosis. Highlights: A novel antithrombolytic protease derived from Euphorbia resinifera latex. The enzyme exhibited fibrinolytic, anticoagulant and antiplatelet activities. Its fibrinogenolytic activity was not abolished by blood circulating inhibitors. The enzyme appears safe for cell viability especially in human blood cells.